Teaching Students in Feminities - Doniyorova Laylo Khudayberdiyevna (Euro Asian Journal Publishing, 2023)
The article aims to highlight the role of infinitives in the Russian language, to note the differences in their pronunciation in spoken and written speech, to focus on the rule of their formation and use.
Keywords: Feminitives; development; professions; colloquial speech